Une prison pour mémoire. Annexes, sources sonores - André, Marc (Sociétés, Espaces, Temps, 2023)
This online collection of archival documents and sound sources comes together as an appendix to Une prison pour mémoire. Montluc, de 1944 à nos jours [A Prison for Memories. Montluc, 1944 to the Present] (Lyon, ENS Éditions, 2022) by historian Marc André. The full digital version of the book is now accessible online : [https://doi.org/10.4000/books.enseditions.42831]. André's Une prison pour mémoire is based on a wealth of archival documents, but it also draws on no less than fifty interviews with living subjects, all conducted by the author between 2012 to 2021, in France and in Algeria. The editors of ENS Éditions and the author believed it was important to give voice to these historical actors whose memories and testimonies dwell far beyond the archive walls, and are therefore unheard, or even silenced. Their testimonies, now made available to the public, allow us to relay a layered history, one that is tied not only to Montluc prison, but also to Algerian immigration and the Algerian War of Independence (1954-1962) as it unfolded in metropolitan France. The author has selected five interviews for this appendix. These form a chorus, each testimony resonating with another. We hear first from the FLN resistor, Salah Khalef, as he shares his memories of the war: the minutiae of his movements and life in France, the remarkable details of the attacks he carried out in the name of the FLN, his time on death row, and the relationship he forged with Claudie Duhamel, a young French student sentenced to ten years in Montluc prison for aiding the FLN. Khalef is followed by René Costechareire, a visitor to the prison. Third, we have Zohra Belghacem's invaluable testimony, of herself as a young Algerian woman detained for her political activism. Khalef returns with his account of the conscientious objectors whom he encountered in Montluc, and finally, Didier Poiraudarrives with his testimony, adding even more depth to the evocations. The voices we hear in the present recount events of the past, but not only. These accounts take us into the historian's workshop. We hear the author confide in his interviewees his own story as he encourages the interlocutors to speak. At times, the discussions turn on questions about the writing of history rather than on those about actual events. What do we make of all of this? What is the role of the witness and that of the historian? Why do we tell each other stories? How do personal stories differ from the historical? Or do they? These are the questions that surface in this volume.